ARABIC, PERSIAN WORDS IN THE WORK OF RABGUZI «KISSASUL-ANBIA» (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2022)
Arabic and Persian words in the language of written monuments make a great contribution to the enrichment of the language, to the enrichment of the vocabulary. Thus, one of the urgent problems is to identify the dynamics of development, changes through linguistic analysis, disclosure of the subtleties of the language of relics as a national treasure, comparison with the modern language, with the same original languages. To this end, the article analyzes Arabic and Persian words in the language of the Rabguzi monument «Kissas-ul-Anbia», which is a monument of medieval writing. Arabic and Persian words, as the nature of the change in our language, had a different character in terms of sound, personality, and meaning. Sound changes and sound coincidences reflect the path of their development. Sound, design features, the composition of the lexical vocabulary, the study of the sentence structure is determined by the language system characteristic of the monument.
Keywords: input words, vocabulary, meaning, religious words, sound, composition.